Burnout, empathy and their relationships: a qualitative study with residents in General Medicine. Issue 3 (2nd April 2016) - Picard, Jeanne; Catu-Pinault, Annie; Boujut, Emilie; Botella, Marion; Jaury, Philippe; Zenasni, Franck
Abstract : Some studies have shown that burnout may have a negative impact on clinical empathy during internship. However, clinical empathy may also be a protective factor, preventing residents from experiencing burnout. Although several quantitative studies have been conducted to examine these relationships between burnout and empathy, no qualitative studies have been carried out. To examine how residents in general practice evaluate the link between burnout and empathy, 24 of them participated in a semi-structured interview. A thematic analysis was carried out to examine residents' discourses and answers to closed questions. The results indicated that residents thought that empathy and burnout were clearly related in different ways. They identified five types of relationship: regulation strategy, empathy as protection, psychological balance/imbalance, fatigue and moderating factors.